The Mosaic Structure of Zeolite Crystals - Qin, Zhengxing; Melinte, Georgian; Gilson, Jean-Pierre; Jaber, Maguy; Bozhilov, Krassimir; Boullay, Philippe; Mintova, Svetlana; Ersen, Ovidiu; Valtchev, Valentin (Angewandte Chemie International Edition, 2016)
Zeolites are widely used in many commercial processes, mostly as catalysts or adsorbents. Understanding their intimate structure at the nanoscale is the key to control their properties and design the best materials for their ever increasing uses. Herein, we report a new and controllable fluoride treatment for the non‐discriminate extraction of zeolite framework cations. This sheds new light on the sub‐structure of commercially relevant zeolite crystals: they are segmented along defect zones exposing numerous nanometer‐sized crystalline domains, separated by low‐angle boundaries, in what were apparent single‐crystals. The concentration, morphology, and distribution of such domains analyzed by electron tomography indicate that this is a common phenomenon in zeolites, independent of their structure and chemical composition. This is a milestone to better understand their growth mechanism and rationally design superior catalysts and adsorbents. Etch it out: A controlled fluoride medium treatment is used to expose the local structure of zeolite crystals. Unexpectedly high concentrations of nanometer‐sized crystalline domains, separated by low‐angle boundaries, were discovered.